OF THE TEACHING OF ACCOUNTING SCIENCE TRADITIONAL FORMS (Web of Discoveries: Journal of Analysis and Inventions, 2024)
Modernizing the educational process in higher educational institutions, improving the quality level of education of professors and teachers, developing teachers ' competence in their profession, increasing the number of literatures on the field, forming skills for independent education in students, forming a system for the effective use of scientific and technical innovations by professors as mature personnel of their field, directing students to creative